Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.2217/nnm.15.160
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of HIV-1 Nanotherapeutics: from in vitro Studies to Clinical Trials

Abstract: Since its discovery almost three decades ago, HIV-1 has grown into the most aggressive pandemic of modern time. Following the implementation of combination antiretroviral therapy, the pathological outcome of HIV infection has substantially improved. However, combination antiretroviral therapy is limited by several factors including, long-term toxicity, serious side effects and complex dosing regimens, and so on. In this regard, researchers have directed their attention toward enhancing current treatment strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 63 publications
0
48
0
2
Order By: Relevance
“…The goal of ARV therapy is to suppress viral replication to the greatest extent possible and for the longest time possible . When used as recommended, CART is extremely effective at reducing viral load; it suppresses viral replication in more than 80% of those beginning treatment . Plasma viral load (the number of HIV RNA copies detected per ml of a patient's blood) is the best stand‐alone, prognostic marker for progression to AIDS .…”
Section: Current Hiv Arv Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The goal of ARV therapy is to suppress viral replication to the greatest extent possible and for the longest time possible . When used as recommended, CART is extremely effective at reducing viral load; it suppresses viral replication in more than 80% of those beginning treatment . Plasma viral load (the number of HIV RNA copies detected per ml of a patient's blood) is the best stand‐alone, prognostic marker for progression to AIDS .…”
Section: Current Hiv Arv Treatmentmentioning
confidence: 99%
“…Furthermore, ARVs are known to have significant adverse side effects, toxicity due to off‐target binding or accumulation, and common and often complicated interactions with other drugs . CART requires once or twice daily doses for the lifetime of the patient, thereby increasing the likelihood that patients will develop serious adverse effects due to long‐term use and making patient compliance to the regimen difficult . Up to 20% of the HIV infected population in the United States has failed to attain full HIV viral load suppression (<200 copies/mL) under sustained CART, a problem that is attributed to patient noncompliance to the treatment regimen .…”
Section: Current Hiv Arv Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings emphasize the need to reconsider strategies for the improvement of NPs, including potential patient selection to identify those most likely to respond to nano-medicines. Nanotechnology-enabled diagnostic and therapeutics based on dendrimers [50][51], gold [52][53], silica [54][55], iron oxide [53,[56][57] and hafnium oxide [58][59] are also currently under clinical analysis, with the majority intended for oncological applications. For example gold NPs decorated with a surface of PEG conjugated to TNFα molecules are in phase I/II trials for solid tumour therapy [60].…”
Section: Major Diseases Leading To Kidney Failurementioning
confidence: 99%
“…At present, developed NFs, ie, optimized combination of NCs and specific drug, were tested using an in vitro model that exhibited a high therapeutic effect and less adverse effect. 1,21,22 Carson et al 23 demonstrated a tunable sustained release of multiclass water-soluble (hydrophilic) anti-HIV drugs, ie, Tef, using polyester-blended electrospun fibers as a potential drug NC. 23 The authors claimed that binding and release of anti-HIV drug was dependent on the affinity level between Tef and the functional groups available on the biocompatible fiber.…”
Section: Kaushik Et Almentioning
confidence: 99%